Growth kinetics of σ-phase precipitates and underlying diffusion processes in CrMnFeCoNi high-entropy alloys. (15th October 2020) - Laplanche, Guillaume
Abstract: Key mechanisms and elementary diffusion processes that control the growth kinetics of σ precipitates in high-entropy alloys were investigated in the present study. For this purpose, an off-equiatomic Cr26 Mn20 Fe20 Co20 Ni14 alloy with an initially single-phase FCC structure was subjected to isothermal heat treatments, which are known to promote the formation of σ phase, i.e., aging between 600 °C and 1000 °C for times ranging from 0.1 h to 1000 h. The growth kinetics of σ precipitates at grain boundaries of the FCC matrix and those located within the interior of the grains were analyzed separately. The latter precipitates are found to grow through direct substitutional diffusion of Cr-solutes towards and Mn, Fe, Co, and Ni away from them and the growth rate of the allotriomorphs can be rationalized by the co llector plate mechanism of interfacial diffusion-aided growth . From the growth-kinetics data obtained in the present study, lattice interdiffusion coefficients as well as diffusivities along crystalline defects were obtained. Above 800 °C, the growth kinetics are dominated by lattice interdiffusion of Cr in the FCC matrix described by D L  = 9.8  ×  10 -4  exp[(-300 kJ/mol)/(R T )] m 2 /s. At lower temperatures, the growth kinetics are enhanced by fast interdiffusion along dislocation pipes, which temperature dependence is given by D D  = 5.0 ×  10 -3  exp[(-205 kJ/mol)/(R T )] m 2 /s. The Cr-diffusivity along σ/FCC interphase boundaries deduced from the thickening kinetics of grain boundary precipitates can be represented by the Arrhenius relationship D I  = 0.5  ×  10 -4  exp[(-145 kJ/mol)/(R T )] m 2 /s, which is similar to that found for grain boundary interdiffusion in metals and alloys. Graphical abstract: Image, graphical abstract